2021
DOI: 10.1063/9.0000082
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of magnetic skyrmions on flat lattices

Abstract: We studied several types of flat lattices with direct exchange and Dzyaloshinskii-Moriya interaction between spins: a honeycomb lattice with 3 nearest neighbours (NN), a square lattice with 4 NN and a hexagonal or triangular lattice with 6 NN. For the analysis of data obtained during the Monte Carlo simulation, a convolutional neural network was used for the recognition of different phases of the spin system which was dependent on simulation parameters such as DMI and external magnetic field (Hz). Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It was shown that the search for GS of spin glasses in a three-dimensional lattice belongs to the NP-complete problem. As a result, many numerical approaches were proposed, such as, for example, genetic algorithms, cluster-exact approximation, renormalization-group approaches, Monte-Carlo methods are developed, such as multicanonical modeling, parallel tempering, the Metropolis algorithm and others [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the search for GS of spin glasses in a three-dimensional lattice belongs to the NP-complete problem. As a result, many numerical approaches were proposed, such as, for example, genetic algorithms, cluster-exact approximation, renormalization-group approaches, Monte-Carlo methods are developed, such as multicanonical modeling, parallel tempering, the Metropolis algorithm and others [2,3,4].…”
Section: Introductionmentioning
confidence: 99%